Library automated acquisitions (Anmol Pubications, 2001)
Contents of material: Introduction. Local area network. CD-ROM network. Wide information service. Library and iformation science. Technologies for cataloguing. Automated bibliographic databases. Cataloguing department perspectives. Management of automated cataloguing. The information server library. Systems migration. Integrated library system.